2019
DOI: 10.1248/bpb.b18-00632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thylakoid-Rich Spinach Extract on the Pharmacokinetics of Drugs in Rats

Abstract: Thylakoid-rich spinach extract is being used as dietary weight-loss supplements in Japan. A recent rat study has suggested that intake of thylakoid-rich spinach extract with dietary oil inhibits dietary fat absorption via binding to bile acids, which promotes excretion of bile acids in feces. While, we confirmed that a serving size of thylakoid-rich spinach extract contains a large amount of calcium (130 mg/5 g). Therefore, using rats, we evaluated whether one-time ingestion of thylakoid-rich spinach extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Nowadays, thylakoid-rich spinach extract is being used as a dietary weight-loss supplement (Saito et al, 2019). Clinical studies have demonstrated that thylakoid-rich spinach extract by suppressing appetite and hunger, promoting satiety and fullness may lead to weight loss (Albertsson et al, 2007;Montelius, Erlandsson, et al, 2014;Rebello et al, 2015;Stenblom et al, 2014;Stenblom et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, thylakoid-rich spinach extract is being used as a dietary weight-loss supplement (Saito et al, 2019). Clinical studies have demonstrated that thylakoid-rich spinach extract by suppressing appetite and hunger, promoting satiety and fullness may lead to weight loss (Albertsson et al, 2007;Montelius, Erlandsson, et al, 2014;Rebello et al, 2015;Stenblom et al, 2014;Stenblom et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thylakoid‐rich spinach extract (concentrated thylakoids extracted from the chloroplasts of spinach leaves) has recently gained attention as a potential therapeutic dietary supplement for the management of obesity due to its beneficial effects in reducing appetite and improving satiety along with enhancing weight loss and fat mass reduction (Albertsson et al, 2007; Saito, Usami, Katoh, & Nada, 2019). The chlorophyll‐containing internal membranes of the green plant chloroplasts, called thylakoids, contain a hundred different membrane proteins, galactolipids, sulpholipids, various vitamins (A, E, and K), and polyphenols/antioxidants, such as chlorophyll, carotenoids, lutein, and zeaxanthin (Albertsson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The change on the solubility of fexofenadine after mixing with R. acetosa extract was tested. The method was modified previously reported method [ 35 , 36 ]. Briefly, 200 μg of fexofenadine and R. acetosa extract were placed in the tube after centrifugal vacuum evaporation of solvent.…”
Section: Methodsmentioning
confidence: 99%